If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(1)/(2)(x-3)+x=17+3(4-x)
We move all terms to the left:
(1)/(2)(x-3)+x-(17+3(4-x))=0
Domain of the equation: 2(x-3)!=0We add all the numbers together, and all the variables
x∈R
1/2(x-3)+x-(17+3(-1x+4))=0
We add all the numbers together, and all the variables
x+1/2(x-3)-(17+3(-1x+4))=0
We multiply all the terms by the denominator
x*2(x-3)-((17+3(-1x+4)))*2(x-3)+1=0
We calculate terms in parentheses: -((17+3(-1x+4)))*2(x-3), so:Wy multiply elements
(17+3(-1x+4)))*2(x-3
2x^2(x-((17+3(-1x+4)))*2(x-3)+1=0
| 20+2u=-10 | | X+16x=96 | | 2c-10=3c | | 35-24=x | | 18•7=x•x+5 | | -1x+6=0.5x | | 63/12=x | | X-5x+4=2x-6+2 | | 2x+7=18+2x | | 80-x-13=15 | | n2-2n-14=-4 | | 150m-125m+42,750=45,675-200m | | 4p+9=(-7p)+2 | | 12−(3x−3)=4(x+5)+4x | | -7x+6=7x-8 | | 3x-15=102 | | 3/5x=150000 | | 63=7/n | | p+3/4=1 | | 5.2g+9=2.2g+21. | | X=1/2x+8/10 | | 4x-6=7x+24 | | 2+5x=-4x+47 | | 45=9/g | | -35n+40= | | 3+3-y=0 | | Z+3-y=0 | | 2+5=-4x+47 | | -8k+8= | | -4a+18= | | -3n-12= | | u/4+5=1 |